EDUCATIONAL INTEGRATIONS IN PRIMARY CLASSES - PEARLS' TASKS AND THE PROBLEM OF ART ANALYSIS (Conferencea, 2023)
In this article, the issue of educational integrations in primary classes - Pirls tasks and artistic analysis is analyzed from a scientific and theoretical point of view.